Subtle difference of [SiMo12O40]4− and [PMo12O40]3− inducing two new distinct Keggin-Ag-(1H-Pyrazole) compounds. Issue 19 (1st October 2016) - Tian, Ai-Xiang; Tian, Yan; Ni, Huai-Ping; Ji, Xue-Bin; Ning, Ya-Li; Hou, Xue; Liu, Guo-Cheng; Ying, Jun
Abstract: Two new inorganic-organic hybrid compounds based on α -Keggin clusters and Ag-(1H-Pyrazole) subunits, [AgL 2 ]4 [SiMo12 O40 ] (1 ) and [AgL 2 ]3 [PMo12 O40 ] (2 ) (L = pyrazole), have been synthesized under hydrothermal conditions and characterized by single crystal X-ray diffraction. In1, there are two kinds of chains, the chains linked by two [AgL 2 ] + clusters and the other linked only by one [AgL 2 ] +, which further connect by sharing [SiMo12 O40 ] 4− anions to construct a 2-D layer. In2, four-supporting [PMo12 O40 ] 3− anions are fused by [Ag(1)L 2 ] + subunits to form a 1-D chain. Through weak interactions of Ag⋯O (3.091 Å) a 2-D supramolecular layer is constructed. Additionally, the electrochemical properties of title compounds and the photocatalytic properties of2 have been studied. Abstract :